A quinoline-based fluorescent labelling for zinc detection and DFT calculations - Nur Syamimi Mohamad,; Ling, Ling Tan; Goh, Choo Ta; Lee, Yook Heng; Nadhratun Naiim Mobarak,; Azwan Mat Lazim,; Suhaila Sapari,; Fazira Ilyana Abdul Razak,; Nurul Izzaty Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
8-carboxamidoquinoline derivatives were gradually investigated as zinc’s label in resolving weak water solubility, poor membrane permeability, and difficulty measuring free Zn2+ ion in cells quantitatively. The potential of 2-oxo-2-(quinolin-8-ylamino)acid (OQAA) as zinc’s label was prepared and characterized spectroscopically. Theoretical and experimental data of OQAA were compared and discussed. The optimized molecular structure, molecular orbital of HOMO-LUMO, energy band gaps, and molecular electrostatic potential (MEP) of OQAA were carried out using the DFT method with Becke-3-Parameter-Lee-Yang-Parr (B3LYP) and 6-31G(d,p) basis set. The intermolecular interaction energy of OQAA-Zn is calculated by using the hybrid method of GEN with a basis set of LANL2DZ for Zn2+ ion and DFT/6-31G(d,p) for OQAA ligand. OQAA exhibited remarkable and excellent fluorescence enhancement selective and qualitatively only for Zn2+ than other metal cations tested (Fe2+, Cu2+, Co2+, Ni2+, Hg2+, Cd2+) under a long wavelength. Job’s plot and 1H NMR titrations indicate OQAA-Zn2+ has a binding ratio at 1:1 stoichiometry (M1L1). Substantial shifting of amide N-H proton to higher chemical shift and intensity of the proton peak of N-H amide decrease abruptly implies that Zn2+ is binding to an amide. These changes confirmed interactions among the ligand OQAA and metal Zn2+ ion. As a result of the benefits discussed, OQAA could effectively and selectively optimize and fabricate for Zn2+ sensors.